2016
DOI: 10.1074/jbc.m116.718544
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Mouse Bitter Taste Receptors Reveals Different Molecular Receptive Ranges for Orthologous Receptors in Mice and Humans

Abstract: One key to animal survival is the detection and avoidance of potentially harmful compounds by their bitter taste. Variable numbers of taste 2 receptor genes expressed in the gustatory end organs enable bony vertebrates (Euteleostomi) to recognize numerous bitter chemicals. It is believed that the receptive ranges of bitter taste receptor repertoires match the profiles of bitter chemicals that the species encounter in their diets. Human and mouse genomes contain pairs of orthologous bitter receptor genes that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
304
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(321 citation statements)
references
References 120 publications
15
304
1
1
Order By: Relevance
“…This study showed, for instance, that T2R3 responds to only a single compound (out of 94 different natural and synthetic compounds tested), whereas T2R14 responds to at least 33 compounds. Conversely, a single bitter compound often can activate multiple different T2Rs 5154 . For example, quinine activates as many as nine different human T2Rs, whereas acetaminophen — an analgesic — stimulates just one human T2R 51 .…”
Section: Chemosensory Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed, for instance, that T2R3 responds to only a single compound (out of 94 different natural and synthetic compounds tested), whereas T2R14 responds to at least 33 compounds. Conversely, a single bitter compound often can activate multiple different T2Rs 5154 . For example, quinine activates as many as nine different human T2Rs, whereas acetaminophen — an analgesic — stimulates just one human T2R 51 .…”
Section: Chemosensory Transductionmentioning
confidence: 99%
“…Presumably, this redundancy evolved to ensure the detection of potentially toxic (bitter-tasting) chemicals and thus prevent the consumption of harmful foods. An evolutionary note in this context is that orthologous receptors in mice and humans often are responsive to very different bitter tastants 54 , which suggests that receptors have been reassigned to ecologically relevant compounds and that the gene family has been subjected to selective pressures 55 . Many T2Rs exhibit functional polymorphisms that result in varying abilities to taste particular compounds 56 , and these polymorphisms may underlie differences in food preference 57 (BOX 3).…”
Section: Chemosensory Transductionmentioning
confidence: 99%
“…This result was consistent with the PTC-tolerant behaviour of colobines. The critical amino acid positions for human TAS2R38 functionality [17] are not altered in the colobine TAS2R38 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…That many bitter compounds do not act through known taste receptors 72 , suggests other receptor families and pathways exist 7,72 . This research also lays the foundation for objectively measuring individual differences—the hallmark of human perception—by not only panelists but also patients.…”
Section: Discussionmentioning
confidence: 99%